THE EFFECT OF OPENNESS ON FOREIGN RESERVES AND GROWTH IN THE EMERGING ECONOMIES - Marcello Spanò (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2012)
This study draws attention to some stylised facts suggesting that the rise of reserves in the Emergingcountries is still partially unexplained. Emerging countries in the last decade seem to have reduced their exposure tothe risk of short term foreign capital outflow, as they have increased GDP growth with little growth in new capitalassets and short term foreign debt. Nevertheless, they have kept raising foreign reserves massively. This workconstructs a model that is able to explain these stylised facts are the result of the same process of globalisation. Asnumerical simulations establish, the optimal solution depends crucially on two structural parameters newlyintroduced in this model, which account for the marginal cost of long term finance and for the competitiveness ofthe domestic industry.